A study of prevalence of issomnia among University Tunku Abdul Rahman students - Tan, Shi Sheng (2011)
Insomnia is common complaints in general population nowadays. It caused by different factors such as physical (cardiovascular), behavior (daytime nap, early retirement to bed), environmental (quietness and brightness environment), and medication (alcohol, central nervous system stimulant). For adolescent, insomnia will affect their healthy and academic performance. In this study, it concentrated on three researches, which are the difference between gender difference towards insomnia, the relationship between insomnia towards stress and depression. There are 100 undergraduate students in University Tunku Abdul Rahman participated in this study. Besides that, three subscale questionnaires which are Insomnia Severity Index (ISI), Stress Perceived Scale (PSS-10) and Patient Health Questionnaire (PHQ-9) used in this study. The research method that used is cross sectional design and the sampling method is convenient sampling. Through the findings, it found that there is no significance difference among gender towards insomnia. But it found that stress and depression is positive correlation with insomnia. In conclusion, both genders have the equal opportunity to have insomnia. But in this study brought important information which is depression and stress is correlated with insomnia, so it can be a guideline for parent and educator to pay attention of the young generation.